Developing holistic Malaysian sports culture index - Sharif, Shamshuritawati; Elumalai, Gunathevan; Mohd Suradi, Nur Riza; Mamat, Shariffah; Aman, Mohd Salleh; Ponnusamy, Vellapandian; Ismail, Hashbullah; Arshad, Mohd Mursyid; Naja Zamri, Nur Najmin; Imran, Farrah Hani (Secholian Publication, 2023)
This research aims to develop a sport culture index to identify the level of sport culture of Malaysian people as well as to quantify other related issues. The data were collected by face to face interviewed questionnaires. The research data were from stratified multi-stage sampling according to states in Malaysia. There were 7857 usable respondents who were at least 13 years old until 60 years old. The correlation index method was applied in the development of the holistic Malaysian Sport Culture index (SCI). The index employs percentage values ranging from 0 to 100; the larger the percentage, the higher the level of sport culture. The result reveals that level of sports participation is 73.3%. By considering the sporting spirit into the model, the Malaysian Sports Culture Index value is 52%. Dividing respondents into several groups according to sport culture index reveals that gender, marital status, age group, level ofeducation, and type of occupation are significantly different. The analyzed results from sport culture index can be utilized to enrich the national policies to create conditions that allow people to cultivate sports in their daily lives. In addition, the approach can be used and adapted for other countries in exploring the development of sports culture towards a sporting nation.